Merkel Cell Carcinoma: A Rare Cause of Hypervascular Nasal Tumor - Azizi, Louisa; Marsot-Dupuch, Kathlyn; Bigel, Pascal; Mzali, Samy; Meyer, Bernard; Tubiana, Jean Michel (American Journal of Neuroradiology, 2001)
Summary: Cutaneous neuroendocrine carcinoma, first described in 1972, is an aggressive disease usually occurring in sun-exposed skin. Other sites have been described, however; such tumors occasionally occur within the nasal fossa. A high rate of metastasis (>30%) explains the poor prognosis. Descriptions of the imaging features of these tumors, mainly located in cutaneous region, are rare. We therefore present the imaging features of two cases of Merkel cell carcinoma involving the sinonasal region, suggestive of a hypervascular tumor.